The shared and separate roles of aposematic (warning) coloration and the co-evolution hypothesis in defending autumn leaves - Lev-Yadun, Simcha (Landes Bioscience, 2010)
The potential anti-herbivory functions of colorful (red and yellow) autumn leaves received considerable attention in the last decade. The most studied and discussed is the co-evolutionary hypothesis, according to which autumn coloration signals the quality of defense to insects that migrate to the trees in autumn. In addition to classic aposematism (repellency due to signaling unpalatability, non profitability of consumption, or danger for whatever reasons) that operates immediately, this hypothesis also proposes that the reduced fitness of the insects is in their next generation hatching in the spring from eggs laid on the trees in autumn. Supporters of the co-evolutionary hypothesis either posited that this hypothesis differs from visual aposematism or ignored the issue of aposematism. Interestingly, other authors that cited their papers considered the co-evolutionary hypothesis as visual aposematism. Recently, the overlap between the co-evolutionary hypothesis and visual aposematism was finally recognized, with the exception of yellow autumn leaves not signaling defense to aphids, which are known to be attracted to yellow leaves. However, the detailed relationships between these two hypotheses have not been discussed yet. Here I propose that the co-evolutionary hypothesis generally equals visual aposematism in red and yellow autumn leaves towards all herbivores except for yellow not operating with aphids. The co-evolutionary signaling extends beyond classic aposematism because it may operate later and not only immediately. The possibility that for yellow autumn leaves the co-evolutionary hypothesis may also operate via olfactory aposematism should not be dismissed.